Anisotropic collisions of dipolar Bose–Einstein condensates in the universal regime. (4th November 2016) - Burdick, Nathaniel Q; Sykes, Andrew G; Tang, Yijun; Lev, Benjamin L
Abstract: We report the measurement of collisions between two Bose–Einstein condensates with strong dipolar interactions. The collision velocity is significantly larger than the internal velocity distribution widths of the individual condensates, and thus, with the condensates being sufficiently dilute, a halo corresponding to the two-body differential scattering cross section is observed. The results demonstrate a novel regime of quantum scattering, relevant to dipolar interactions, in which a large number of angular momentum states become coupled during the collision. We perform Monte-Carlo simulations to provide a detailed comparison between theoretical two-body cross sections and the experimental observations.